Hepatic regeneration and functional recovery following partial liver resection in an experimental model of hepatic steatosis treated with omega‐3 fatty acids. Issue 5 (1st March 2013) - Marsman, H. A.; de Graaf, W.; Heger, M.; van Golen, R. F.; ten Kate, F. J. W.; Bennink, R.; van Gulik, T. M.
Abstract Background Omega‐3 fatty acids (FAs) have been shown to reduce experimental hepatic steatosis and protect the liver from ischaemia–reperfusion injury. The aim of this study was to examine the effects of omega‐3 FAs on regeneration of steatotic liver. Methods Steatosis was induced in rats by a 3‐week methionine/choline‐deficient diet, which was continued for an additional 2 weeks in conjunction with oral administration of omega‐3 FAs or saline solution. Steatosis was graded histologically and quantified by proton magnetic resonance spectroscopy (1H‐MRS) before and after the diet/treatment. Liver function was determined by 99mTc‐labelled mebrofenin hepatobiliary scintigraphy (HBS). In separate experiments, the hepatic regenerative capacity and functional recovery of omega‐3 FA‐treated, saline‐treated or non‐steatotic (control) rats were investigated 1, 2, 3 and 5 days after partial (70 per cent) liver resection by measurement of liver weight change and hepatocyte proliferation (Ki‐67) and HBS. Results Severe steatosis (over 66 per cent) in the saline group was reduced by omega‐3 FAs to mild steatosis (less than 33 per cent), and hepatic fat content as assessed by 1H‐MRS decreased 2·2‐fold. 99mTc‐mebrofenin uptake in the saline group was more than 50 per cent lower than in the control group, confirming the functional effects of steatosis. 99mTc‐mebrofenin uptake and regenerated liver mass were significantly greater in the omega‐3 group compared with the saline group on days 1 and 3. The posthepatectomy proliferation peak response was delayed until day 2 in saline‐treated rats, compared with day 1 in the omega‐3 and control groups. Conclusion Omega‐3 FAs effectively reduced severe hepatic steatosis, which was associated with improved liver regeneration and functional recovery following partial hepatectomy.